New cancer cases at the time of SARS-Cov2 pandemic and related public health policies: A persistent and concerning decrease long after the end of the national lockdown. (June 2021) - Kempf, Emmanuelle; Lamé, Guillaume; Layese, Richard; Priou, Sonia; Chatellier, Gilles; Chaieb, Hedi; Benderra, Marc-Antoine; Bellamine, Ali; Bey, Romain; Bréant, Stéphane; Galula, Gilles; Taright, Namik; et al.
Abstract: Introduction: The dissemination of SARS-Cov2 may have delayed the diagnosis of new cancers. This study aimed at assessing the number of new cancers during and after the lockdown. Methods: We prospectively collected the clinical data of the 11.4 million patients referred to the Assistance Publique Hôpitaux de Paris Teaching Hospital. We identified new cancer cases between 1st January 2018 and 31st September 2020 and compared indicators for 2018 and 2019 to 2020 with a focus on the French lockdown (17th March to 11th May 2020) across cancer types and patient age classes. Results: Between January and September, 28, 348, 27, 272 and 23, 734 new cancer cases were identified in 2018, 2019 and 2020, respectively. The monthly median number of new cases reached 3168 (interquartile range, IQR, 3027; 3282), 3054 (IQR 2945; 3127) and 2723 (IQR 2085; 2, 863) in 2018, 2019 and 2020, respectively. From March 1st to May 31st, new cancer decreased by 30% in 2020 compared to the 2018–19 average; then by 9% from 1st June to 31st September. This evolution was consistent across all tumour types: −30% and −9% for colon, −27% and −6% for lung, −29% and −14% for breast, −33% and −12% for prostate cancers, respectively. For patients aged <70 years, the decrease of colorectal and breast new cancers in April between 2018 and 2019 average and 2020 reached 41% and 39%, respectively. Conclusion: The SARS-Cov2 pandemic led to a substantial decrease in new cancer cases. Delays in cancer diagnoses may affect clinical outcomes in the coming years. Highlights: A national lockdown occurred in France between 17th March to 11th May 2020. In Paris, new cancer cases in March–May 2020 was 33% lower than in 2018–2019. In Paris, new cancer cases in June–September 2020 was 19% lower than in 2018–2019. In January–September 2020, the monthly new cases median was 1949 (IQR 1586; 2045). Less new cancers have been seen since the beginning of the SARS-Cov2 pandemic.